The Role of Financial Literacy, Peer Influence, and Digital Transformation in Financial Decision-Making - Turnip, Elsa Nesiana Imanuela; Panjinegara, Prakarsa (Harmony Management: International Journal of Management Science and Business, 2025)
Financial decision-making among university students has become a critical issue in the digital era, requiring adequate financial literacy and adaptive skills. This study aims to explore how students at Lampung Uni-versity make financial decisions by examining three main factors: financial literacy, peer influence, and digital transformation. A qualitative phenomenological approach was employed to capture students’ subjective experiences regarding their thought processes, considerations, and social dynamics influencing financial choices. Data were collected through in-depth interviews with participants selected using purposive random sampling and analyzed using thematic coding with NVivo 12 Pro software. The findings indicate that financial literacy serves as a cognitive foundation, enabling students to assess risks, prioritize ex-penditures, and develop basic financial management strategies. Peer influence affects financial decisions through social norms, social comparisons, and peer recommendations. Meanwhile, digital transformation facilitates access to information, accelerates transactions, and shapes new consumption and investment patterns among students. The interaction of these three factors contributes to the formation of com-prehensive financial awareness. This study provides insights for enhancing financial education and promoting rational financial behaviors among young adults.